2020
DOI: 10.1126/science.aay9792
|View full text |Cite
|
Sign up to set email alerts
|

Seeing around corners: Cells solve mazes and respond at a distance using attractant breakdown

Abstract: During development and metastasis, cells migrate large distances through complex environments. Migration is often guided by chemotaxis, but simple chemoattractant gradients between a source and sink cannot direct cells over such ranges. We describe how self-generated gradients, created by cells locally degrading attractant, allow single cells to navigate long, tortuous paths and make accurate choices between live channels and dead ends. This allows cells to solve complex mazes efficiently. Cells’ accuracy at f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(103 citation statements)
references
References 39 publications
3
100
0
Order By: Relevance
“…We also made a quasi-steady state approximation for the TAF dynamics, which simplified our analysis by making the TAF field linear. TAF dynamics may be more complicated in reality, however, and can play a more significant role in the migratory dynamics: cell-induced gradients, for instance, can provide time-dependent guidance cues for tip cells, and will generate spatial heterogeneities in the TAF gradient that were not considered here (Tweedy et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…We also made a quasi-steady state approximation for the TAF dynamics, which simplified our analysis by making the TAF field linear. TAF dynamics may be more complicated in reality, however, and can play a more significant role in the migratory dynamics: cell-induced gradients, for instance, can provide time-dependent guidance cues for tip cells, and will generate spatial heterogeneities in the TAF gradient that were not considered here (Tweedy et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we analyzed tip and stalk cell dynamics in an idealized condition where the TAF concentration was at steady state. In more biologically relevant scenarios, however, the TAF field is unlikely to match the profiles investigated in Table II and its dynamics will likely be more complex: for example, cells may degrade the chemoattractant and create cell-induced gradients [57]. It may therefore be necessary to include such dynamics in the snail-trail modeling framework when it is used to analyze experimental results.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we assume that the system contains a generic chemoattractant (a TAF) whose concentration is denoted by c(x, y, t ). In general, the value of c is governed by a differential equation that may include terms corresponding to diffusion and/or uptake by tip and stalk cells [46,56,57]. However, in this article we are most interested in determining appropriate equations for describing cell movement and proliferation.…”
Section: Snail-trail Model Development In 2dmentioning
confidence: 99%
“…Another emerging aspect of tumor invasion is the decision-making ability of cancer cells when they are faced with branching tracks. The ECM is like a maze for cancer cells migrating inside, and a recent study demonstrated a surprising ability of pancreatic cancer cells to navigate efficiently inside a microfluidic-based maze (Tweedy et al, 2020). Another recent study on immune cells also unveiled that the cell nucleus and microtubule-organizing center can act as a gauge to efficiently navigate neutrophil transmigration in matrices with differently sized pores (Renkawitz et al, 2019).…”
Section: Microfluidic Channelmentioning
confidence: 99%